Increasing axial parenchyma fraction in the Malagasy Magnoliids facilitated the co‐optimisation of hydraulic efficiency and safety. Issue 3 (27th October 2020) - Aritsara, Amy Ny Aina; Razakandraibe, Vonjisoa M.; Ramananantoandro, Tahiana; Gleason, Sean M.; Cao, Kun‐Fang
Summary: The evolution of angiosperms was accompanied by the segregation and specialisation of their xylem tissues. This study aimed to determine whether the fraction and arrangement of parenchyma tissue influence the hydraulic efficiency–safety trade‐off in the basal angiosperms. We examined xylem anatomical structure and hydraulic functioning of 28 woody species of Magnoliids in a tropical rainforest of Madagascar and reported, for the first time, quantitative measurements that support the relationship between vessel‐to‐xylem parenchyma connectivity and the hydraulic efficiency–safety trade‐off. We also introduced a new measurement – the distance of species from the trade‐off limit – to quantify the co‐optimisation of hydraulic efficiency and safety. Although the basal angiosperms in this study had low hydraulic conductivity and safety, species with higher axial parenchyma fraction ( APf ) had significantly higher hydraulic conductivity. Hydraulic efficiency–safety optimisation was accompanied by higher APf and vessel‐to‐axial parenchyma connectivity. Conversely, species exhibiting high ray parenchyma fraction and high vessel‐to‐ray connectivity had lower Ks and were further away from the hydraulic trade‐off limit line. Our results provide evidence that axial parenchyma fraction and paratracheal arrangement are associated with both enhanced hydraulic efficiency and safety.